Law, Lies and Letter Writing: An Analysis of Jerome and Augustine on the Antioch Incident (Galatians 2:11–14) - Myers, Jason A. (Scottish journal of theology, 2013)
Various critics of the New Perspective on Paul (NPP) often highlight the lack of church tradition as one deficiency of the various interpretations of Paul. To some, the lack of church history automatically renders such newer interpretations suspect. In turn critics of the NPP often turn to the reformers such as Calvin and Luther to defend the traditional reading of Paul and trace this traditional reading back to Augustine. For the critics, church tradition stands on the side of the traditional reading.This article seeks to highlight an often neglected early church view on one aspect of the NPP, that of Paul and the Law. This article highlights one of the fiercest exchanges between two church fathers. Through a series of letters, Jerome and Augustine corresponded on Jerome's interpretation of Galatians 2 and the Antioch incident. For Augustine the pastor, nothing less than the veracity of scripture was at stake and Augustine mounts a defence of Paul's actions in Galatians 2 in response to Jerome's insistence of an agreed-upon lie between Peter and Paul. In the process of Augustine's rebuttal of Jerome, he notes that Paul followed the law without ‘pretence’ and that there was a period in early Christianity where Jewish Christians practised law observance. Augustine highlights the divine origin of the Mosaic law, which renders a positive role for the law in early Christianity, and notes that the negative critique of the law comes within the context of a Gentile audience, but did not have implications for Jewish Christians. Augustine rightly notices and raises the important context of Paul's negative statements on the law and offers a nuanced discussion of Paul's treatment of the law.Augustine notes some of the important conclusions drawn by the NPP, namely a positive view of the law and its practice by Paul and other Jewish Christians. He also notes the various ways the law functions in Jewish and Gentile contexts. Such a positive view of Paul and the law may appear striking to many, but must be considered by those who are otherwise critical of the NPP. This article shows that there was at least one voice, among others, within the early church which advocated for a positive reading of Paul and the law. The history of interpretation of Galatians 2 offers many insights for contemporary Pauline scholars which ought to be heeded in future discussions. This article, by highlighting the exchange between Jerome and Augustine, seeks to give the NPP a historical ‘rootedness’ and placement within the history of interpretation.